Pelatihan Daur Ulang Sampah Di Kelurahan Sudajaya Hilir - Erik Candra Pertala (Alahyan Jurnal Pengabdian Masyarakat Multidisiplin, 2023)
The waste recycling training aims to increase people's knowledge, skills, and awareness about the importance of waste recycling to protect the environment and economy. Training participants will be given knowledge about waste processing techniques into recycled products, such as handicrafts, shopping bags, and building materials. In addition, participants will also be given knowledge about the importance of maintaining environmental cleanliness. It is hoped that waste recycling training can help overcome waste management problems that exist in the community, improve community welfare through the development of the recycling industry, and encourage the creation of an environmentally conscious society and care for the surrounding environment. Waste recycling training is very important to do and needs to be encouraged so that people can be more concerned and responsible for the environment.